Functional impairment and health care utilization among HIV-infected men who have sex with men: the relationship with depression and post-traumatic stress - O’Cleirigh, Conall (2009)
This study examined the relationship of post-traumatic and depressive symptom severity with measures of health-related quality of life (HRQOL), and health care utilization in a sample of 503 HIV-infected men who have sex with men (MSM) recruited in their primary HIV care setting. Participants completed computer assisted assessments of mood and anxiety, HRQOL, and HIV treatment. Peripheral blood CD4 (T helper) lymphocyte count, plasma HIV RNA concentration, and number of medical appointments were extracted from an electronic medical record. Controlling for demographics, disease stage, and antiretroviral medication, post-traumatic stress and depression symptoms accounted for significant variation in general health estimates, and in pain, role, and work-related impairment. Additionally, in multivariable models, post-traumatic stress and depression severity accounted for significant variation in health care utilization whereas symptoms and indices of HIV disease progression did not. These results extend the current research by providing evidence of the relationship between post-traumatic stress and depression symptom severity with measures of functional impairment and health care utilization in a relatively healthy, urban cohort of HIV-infected MSM.